2016
DOI: 10.1007/s11356-016-7589-x
|View full text |Cite
|
Sign up to set email alerts
|

Free radical reaction characteristics of coal low-temperature oxidation and its inhibition method

Abstract: Study on the mechanism of coal spontaneous combustion is significant for controlling fire disasters due to coal spontaneous combustion. The free radical reactions can explain the chemical process of coal at low-temperature oxidation. Electron spin resonance (ESR) spectroscopy was used to measure the change rules of the different sorts and different granularity of coal directly; ESR spectroscopy chart of free radicals following the changes of temperatures was compared by the coal samples applying air and blowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(29 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The heat released by the reaction is used to break new bonds, producing more active groups. 35 Active aliphatic hydrocarbons can still generate a small amount of peroxides (−C–O–O) in a lean-oxygen environment and generate heat at the same time. And because H 2 O is mainly derived from the hydroxyl groups of aliphatic hydrocarbons combined with a large amount of hydrogen, during the development of coal spontaneous combustion, most of the oxygen-containing functional groups are consumed to generate carbon radicals (R).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The heat released by the reaction is used to break new bonds, producing more active groups. 35 Active aliphatic hydrocarbons can still generate a small amount of peroxides (−C–O–O) in a lean-oxygen environment and generate heat at the same time. And because H 2 O is mainly derived from the hydroxyl groups of aliphatic hydrocarbons combined with a large amount of hydrogen, during the development of coal spontaneous combustion, most of the oxygen-containing functional groups are consumed to generate carbon radicals (R).…”
Section: Results and Discussionmentioning
confidence: 99%
“…These free radicals have high chemical reactivities and can easily interact with O 2 in air to release heat. The accumulation of heat leads to a continuous increase in the coal temperature, finally triggering coal spontaneous combustion 14,30–32 . Therefore, the oxidation reactivity can be reflected by free radicals in the coal.…”
Section: Resultsmentioning
confidence: 99%
“…The spontaneous combustion duration of coal is shortened, and the combustion area is expanded, which seriously threatens safety production in mines 11–13 . Li put forward the free radical reaction theory, considering that free radicals triggered coal spontaneous combustion 14 . Xi et al confirmed that coal oxidation could be inhibited by interrupting free radical chain reaction 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For internal moisture, physical-state moisture exists on the coal particle surface, and there is a moisture layer on the surface, which reduces the porous structure and specific surface area and affects the oxygen diffusion; hence, the low-temperature oxidation of coal is inhibited [4,14]. On the other hand, chemical-bound moisture can participate in the formation and decomposition of a carbon-oxygen complex during the spontaneous combustion of coal [15][16][17][18]. Beamish et al [19] investigated the effects of moisture content on the R 70 self-heating rate contents and found there was a critical level of moisture content at approximately 40-50% of the moisture-holding capacity of the coal, above which the heat produced by oxidation was dissipated by moisture evaporation and coal self-heating was significantly delayed.…”
Section: Introductionmentioning
confidence: 99%